2020
DOI: 10.1109/access.2019.2962390
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fault Detection Model Based on Atanassov’s Interval-Valued Intuitionistic Fuzzy Sets, Belief Rule Base and Evidential Reasoning

Abstract: In engineering practice, fault detection, with the fundamental characteristics of randomness, uncertainty, and great damage, has attracted much attention from academia. The chief aim of this paper is to research the problem of flush air data sensing (FADS) system, an advances airborne sensor, with Atanassov's interval-valued intuitionistic fuzzy sets (AIVIFSs), belief rule base (BRB) and evidential reasoning (ER). First of all, this paper proposes some relevant concepts and similarity calculation operators bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…While the value range of the score function and accuracy function developed by Xu is [-1,1] and [0.1], respectively, it is observed that the value ranges of the score functions and accuracy functions developed later differed. While the maximum values obtained by accuracy ranking functions in [17,24] and score function [19] are smaller than 1, the maximum value obtained by score function [13] is bigger than 1. Besides, minimum and maximum values calculated by accuracy functions in [12,15,17,18] are equal, and this equality is unacceptable.…”
Section: A Comparison Of Ranking Functions For Ivifsmentioning
confidence: 81%
See 4 more Smart Citations
“…While the value range of the score function and accuracy function developed by Xu is [-1,1] and [0.1], respectively, it is observed that the value ranges of the score functions and accuracy functions developed later differed. While the maximum values obtained by accuracy ranking functions in [17,24] and score function [19] are smaller than 1, the maximum value obtained by score function [13] is bigger than 1. Besides, minimum and maximum values calculated by accuracy functions in [12,15,17,18] are equal, and this equality is unacceptable.…”
Section: A Comparison Of Ranking Functions For Ivifsmentioning
confidence: 81%
“…Jia et al [19] introduced a score function (. ) J in Equation ( 24) utilized to quantify the information included in IVIFV with the idea of p-norm.…”
Section: Jia Et Al [19]'s Ranking Methods Of the Ivifvmentioning
confidence: 99%
See 3 more Smart Citations